Significance and Guidance between Qur’anic Verses and Arabic Dictionaries - Boukhmis, Soufian; Karoui, Zahira (Milev Journal of Research and Studies, 2022)
The study aims to determine the extent to which the significance of words in Arabic dictionaries is linked to their significance in the Qur'an, and that is why we chose two words that have a great impact on the lexical and Qur'anic lessons, and in order to reach the desired end, the choice was signed on the words "semantic" (the Hidaya) for their weight within these two scientific fields (dictionary, Qur'an), which is by comparing and approaching the significance of the two words (semantics, guidance) in the Arabic dictionaries - ancient and modern - with what their significance holds in the holy Qur'anic verses.